Prostatic pseudohyperplasia carcinoma. Experiences and criteria. - Ileana Franco Zunda; Alfredo B. Quiñones Ceballos; Antonio L. Moreno Otero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: Prostatic deseases are a havoc in male population older than 45 years old. Pseudohyperplastic carcinoma is a non frecuent variety and hard to diagnose. Objective: to reevaluate prostatic hyperplasia diagnoses to identify pseudohyperplastic carcinomas. Methods: retrospective study in which the prostatic hyperplasia diagnoses of 2004 were reevaluated in the Uiversitary Hospital ¨Dr. Gustavo Aldereguia Lima¨, considering as a basis the criteria given by Julian Arista -Nasr, evaluated in his 2000 series, to determine which of them corresponded to pseudohyperplastic carcinomas. Results: of the 51 reevaluated cases, 4 pseudohyperplastic carcinomas were found, the neoplasia was arranged in nodules of well defined edges resembling glandular hyperplasia areas, 100% showed nucleomegaly, with cromatine preferably lax, as well as evident nucleoli ocassionally inconspicuous, pale pink dyed, cytoplasm of great size and amphophil. Conclussions: the cytologycal changes were the definite criteria to establish the pseudohyperplastic carcinoma diagnosis.